Multi-Analytical Characterization of Illuminated Choirbooks from the Royal Audience of Quito - Martha Romero-Bastidas; Katherine Guacho-Pachacama; Carlos Vásquez-Mora; Fernando Espinoza-Guerra; Rita Díaz-Benalcázar; Johanna Ramírez-Bustamante; Luis Ramos-Guerrero (Heritage)
Choirbooks are historical heritage manuscripts used for the performance of vocal music in religious ceremonies in colonial times. This study aimed to understand the characteristics of choirbook manuscripts produced in the Real Audiencia de Quito during the 17th century. The methodology combined non-invasive techniques, such as infrared false-color imaging (IRFC) and X-ray fluorescence (XRF), together with spot analysis by scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) and Fourier transform infrared spectroscopy with attenuated total reflection (FTIR-ATR). The analytical results revealed the use of pumice, chalk and lime carbonate as support materials in the manufacturing process and surface treatment of the parchment. In the illuminations, three pictorial techniques based on protein, polysaccharide and lipid binders were recognized, establishing that the pigments used with greater regularity in the illuminations were vermilion, minium, verdigris, orpiment, azurite, and indigo, preferably in a pure state. Materials used less regularly were also identified, such as yellow ochre, saffron, smalt, red ochre, and bone black, among others. Regarding the vulnerability of the pictorial materials, it was determined that, although most of the pigments exhibit chemical stability, they present some vulnerabilities associated with their intrinsic composition and the medium that contains them.